2017
DOI: 10.3168/jds.2016-12312
|View full text |Cite
|
Sign up to set email alerts
|

Milking time and risk of over-milking can be decreased with early teat cup removal based on udder quarter milk flow without loss in milk yield

Abstract: Increasing the milk flow rate at which milking is terminated can shorten milking time and increase milking efficiency. The effects on milk yield and composition have not been fully investigated when the take-off is set at the udder quarter level and independent of feeding during milking. The objective of this study was to investigate the effect of 3 take-off levels at the udder quarter level (0.06, 0.3, and 0.48 kg/min) applied with or without feeding during milking on milking time, milk yield, the degree of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 30 publications
(40 reference statements)
11
33
2
Order By: Relevance
“…Although this study was not designed to test the effect of SM on milk production, our results can help in the interpretation of previous studies and in the design of new studies to explore this relationship. Krawczel et al (2017) found no differences in daily milk yield between 0.06, 0.3, and 0.48 kg/min switch-points applied at the quarter level but did not measure SM.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Although this study was not designed to test the effect of SM on milk production, our results can help in the interpretation of previous studies and in the design of new studies to explore this relationship. Krawczel et al (2017) found no differences in daily milk yield between 0.06, 0.3, and 0.48 kg/min switch-points applied at the quarter level but did not measure SM.…”
Section: Discussionmentioning
confidence: 63%
“…When milk flow rate switch-points were applied at the quarter level, our predicted reduction in MD Q (2.0 min from MFR0.2 Q to MFR1.0 Q ) was considerably larger than the reduction in MD U for the same switch-point applied at the udder level (1.4 min from MFR0.2 Q to MFR1.0 Q ). A study by Krawczel et al (2017) reported a 0.9-min (12%) reduction in MD between 0.06 kg/ min and 0.48 kg/min switch-point settings. Although the switch-point settings used in our study were not the same as those used by Krawczel et al (2017), the reduction in MD was comparable: 0.4-min (9%) reduction in MD Q between MFR0.2 Q and MFR0.4 Q , and 1.1min (25%) reduction between MFR0.2 Q and MFR0.6 Q.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations